International relations in Southeast Asia : the struggle for autonomy - Weatherbee, Donald E. (Asia in world politics., 2014)
"Offers a clear and comprehensive introduction to the international relations of contemporary Southeast Asia. The author analyzes the Southeast Asian states' efforts to adapt to a regional international environment that is characterized by the security demands of the war on terrorism; the economic demands of globalism; and the political demands of nontraditional issues such as democracy, human rights, the environment, and gender. These shifting dynamics take place in a broader framework of diminished U.S. power and enhanced Chinese influence that could well undermine Southeast Asia's autonomy"--